A Amazônia e a formação do Estado Imperial no Brasil: unidade do território e expansão de domínio - NUNES, Francivaldo Alves (Universidade Federal do Pará, 2017)
Our proposal is to analyze the formation of the Amazon region in association with the formation of the Brazilian Empire, based in two questions: the expansion of the structure of domination by the Court of Rio de Janeiro and the unity of the national territory as one of the goals of this expansion. In this paper we propose to show that the Amazonian space is understood by the Brazilian authorities in two ways: as a space necessary to the unity of the Brazilian territory, given the international interest it attracted, and as a way to expand the national interests.